PHONEMIZATION PATTERNS IN THE TOMBATU LANGUAGE OF SOUTHEAST MINAHASA: A SYSTEMATIC REVIEW - Liuw, Jola; Gosal, Nicolas; Lasut, Conny R. (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This research aims to examine systematic sound changes that influence certain sound patterns and classes through segmentation of language sounds grouping patterns and sound classes of the Tombatu language Moreover this paper also focuses on analyzing the phonological process explaining variations in speech sounds describing the process of changes in language sounds and compiling standard phonetic formulas The techniques for providing data were tapping techniques skillful listening techniques recording techniques note taking techniques and using the Tombatu Language Vocabulary instrument based on the Swadesh list 200 Vocabulary In terms of data analysis several techniques are conducted according to Larry Hyman s phoneme concept minimal pairs 1975 and by grouping distinctive characteristics by Chomsky and Halle in Yusuf 1998 Jakobson and Trubetzkoy in Kenstowicz 2007 The results showed that Tombatu language there are no phonemes f v q z x and on the contrary there are other phonemes which are characteristic of the Tombatu language but do not differentiate the meaning such as phonemes and there are diphthong phonemes There are 19 consonant phonemes 6 vowel phonemes 9 diphthong phonemes i ai oi ui and aw iw uw ew ow Distinctive characteristics of BT phonemes especially typical BT phonemes languid fricative voiced alveolar lamino suddenly loose stop burst voiced apico prepalatal wide languid lateral voiced apico prepalatal tight loose suddenly inhibited eruption sound apico prepalatal < p>